Evaluation of Physical Stability of Carbopol Gel Containing Curcumin under Temperature Variations - Najwa Athifah Tsamarah Umar; Mohamad Aprianto Paneo; Nurain Thomas; Fika Nuzul Ramadhani; Lisa Efriani Puluhulawa (Jurnal Literasi Mandiri, 2026)
Inflammation is a biological response to tissue damage characterized by swelling, redness, pain, and increased local temperature. Curcumin is known to possess anti-inflammatory activity by inhibiting inflammatory mediators such as tumor necrosis factor-alpha (TNF-α). This study aimed to develop a Carbopol-based curcumin gel formulation and evaluate its physical characteristics and stability under various temperature conditions. This research employed a laboratory experimental method including gel base optimization, formulation of curcumin gel with concentration variations (1%, 2%, and 3%), physical evaluation, and stability testing using a temperature stress test at low and high temperatures. The results showed that Carbopol 0.5% was the optimal gel base. All formulations met the required physical characteristics, including homogeneity, pH, viscosity, spreadability, and adhesiveness. Stability testing indicated that the formulations were organoleptically stable and relatively stable chemically, although viscosity decreased at higher temperatures. Therefore, Carbopol-based curcumin gel has potential as a stable and effective topical preparation.